The effects of benzene inhalation exposure and pyridoxine deficiency in male Bb6(BCb3(BFb1 (Bmices - Chanthana Tangjarukij; Mathuros Ruchirawat; Zelikoff, Judith T.; Thammarat Koottatep; Settachan, Daam; S and T Postgraduate Education and Research Development Office (PERDO), Ministry of Education, Thailand (Pathum Thani, Thailand : Asian Institute of Technology, 2009)
The objective of this study was to explore the general effects of pyridoxine deficiency in male Bb6(BCb3(BFb1 (Bmice, as well as specific effects on the hematological system, immune function, and hepatic cytochrome P450 enzymes. In addition, a possible mechanism of action underlying pyridoxine deficiency on benzene toxicity was studied by examining hepatic enzymes involved in benzene metabolism and formation of benzene metabolites. Male Bb6(BCb3(BFb1 (Bmice were fed either a pyridoxine-deficient (PD) or control (CD) diet (containing 0 and 7 mg pyridoxine-HC1/kg diet, respectively) for 8 or 13 weeks and subsequently administered 500 ug pyridoxine-HC1 (via intraperitoneal [IP] injection) daily for 2 (PD-S2 and CD-S2) or 3 (PD-S3 and CD-S3) consecutive days thereafter following the end of each period. The results demonstrated that erythrocyte aspartate aminotransferase activity coefficient (EAST-AC) values were significantly higher in PD mice than in CD mice, reflecting the pyridoxine-deficient status of the animals; EAST -AC levels rebounded after supplementation. PD mice had significantly lower weight gains; hemoglobin (HOB) levels, mean corpuscular volume (MCV); and, hematocrit (HCT) values. Although PD mice had significantly lower levels of peripheral white blood cells (WBC) compared to CD mice after 8 weeks, no significant effects were observed after 13 weeks. Moreover, no significant effects were observed on either T- or B-Iymphocyte proliferation. Three days of pyridoxine supplementation restored HOB levels in PD mice to normal; the supplementation also increased HCT and MCV levels, but not to those seen in the CD mice. Although hepatic CYPIAI protein expression was not affected by pyridoxine deficiency, a significant increase in activity of the enzyme in PD mice could be reversed with pyridoxine supplementation. In a second series of studies, the effect of pyridoxine deficiency on benzene toxicity was examined. In background studies, weanling mice were fed the control diet for 16 weeks and then exposed (by nose-only inhalation) to benzene at 0, 10, 40, or 100 ppm, 4 hours/day on 10 consecutive days. Dose-dependent reductions in relative spleen and thymus weights, as well as a decrease in B-Iymphocyte proliferation were observed. In addition, hepatic CYP2E1 protein expression and activity tended to increase. Changes in hematological profiles, including increased neutrophils numbers, and decreased WBCs and MCV appeared to be independent of benzene dose. Having established baseline effects from the benzene exposures, sets of weanling mice were fed the CD or PD mice diets and then also nose-only exposed to 100 ppm benzene for 4 hours/day on 10 consecutive days. PD mice exposed to 100 ppm benzene had a significantly decreased body weights and splenic and thymic indices, but increased relative liver indices, compared to PD-0 ppm or CD-100 ppm counterparts. While the percentages of blood neutrophils increased in the PD-100 ppm mice, decreases in WBC numbers, percentage HCT, HGB, and MCV were also clearly observed; hepatic CYP2E1 protein and activity were significantly increased in these same mice as well. In a third set of studies, CD and PD mice (upon completion of 13 weeks on diets) were IP-treated with com oil vehicle or 100, 200, or 400 mg benzene/kg BW on each of 3 consecutive days. Both CD and PD mice treated with benzene had a dose-dependent increase in their percentage of blood neutrophils, but decreases in WBC numbers and percentages of blood lymphocytes, monocytes and basophils. Effects in PD mice were greater than those in the CD mice, as well as with regard to decreases in HOB, HCT, and MCV and increases in platelet numbers. Overall, urinary trans-trans muconic acid (t,t-MA) excretion patterns were similar to those for s-phenyl mercapturic acid (s-PMA); however, the PD mice produced slightly lower levels of each metabolite than did CD mice. In the first 24 hours after benzene administration, the highest levels of both t,t-MA and s-PMA were detected in the urine of CD mice; these were seen to have increased in a dose-dependent fashion. In contrast, PD mice presented an inverse dose-response pattern, in which treatment with 400 mg benzene/kg induced lower metabolite levels than exposure to 200 mg/kg. These studies clearly demonstrate that deficiency of pyridoxine can cause extensive alterations in benzene toxicity that could be mediated (at least in part) via effects on hepatic CYP2E1 protein expression/activity; still, modulation by PD of other aspects of benzene metabolism could also have played a role in the effects observed heres
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Environmental Engineering and Management
Thesis (Ph.D.) - Asian Institute of Technology - Chulabhorn Research Institute - Mahidol University, 2009
Keywords: Vitamin B6 -- Environmental aspects; Benzene -- Environmental aspects